A novel investigation on horizontal and 3D elliptical ultrasonic vibrations in rotary ultrasonic surface machining of carbon fiber reinforced plastic composites. (April 2020) - Wang, Hui; Hu, Yingbin; Cong, Weilong; Hu, Zhiyong; Wang, Yeqin
Highlights: 3D elliptical ultrasonic vibration is developed for surface machining of CFRP. RUSM with 3D elliptical ultrasonic vibration generates the smallest cutting force. The horizontal and 3D elliptical ultrasonic vibrations improve the machining performance. The critical ultrasonic frequency for grain-trajectory overlapping is analyzed. The horizontal and 3D elliptical ultrasonic vibrations reduce the generated defects. Abstract: Carbon fiber reinforced plastic (CFRP) composites were attractive in lots of applications, in which surface machining processes were always needed after molding fabrication processes to achieve the final functional surface geometry with desired accuracy. To improve the effectiveness and efficiency, rotary ultrasonic surface machining (RUSM) had been applied in processing CFRP composites. With the assistance of vertical ultrasonic vibration in RUSM, cutting forces were significantly reduced, but the surface roughness was increased. To improve the surface conditions and additionally reduce the cutting force for RUSM, the applied ultrasonic vibration should be aligned with surface generation direction (namely horizontal feeding direction). Up till now, there were no reported investigations on RUSM with horizontal vibration and 3D elliptical ultrasonic vibration, formed from the combination of horizontal and vertical ultrasonic vibrations. In this investigation, the horizontal and 3D elliptical ultrasonic vibrations were applied in RUSM. The comparisons among RUSM with 3D elliptical ultrasonic vibration, RUSM with horizontal ultrasonic vibration, and the surface machining without ultrasonic vibration on machining performance and surface quality were conducted. Experimental results showed that RUSM with horizontal ultrasonic vibration reduced both cutting force and surface roughness. With the application of 3D elliptical ultrasonic vibration, both cutting force and surface roughness can be further decreased. The critical horizontal ultrasonic frequency for the overlapping of abrasive grains' trajectories was analyzed. The mechanisms of RUSM with both horizontal and 3D elliptical ultrasonic vibrations and the reasons for both cutting force decreasing and surface roughness decreasing were also investigated.